The characteristics of corn silk (Zea mays L.) herbal drinks tea with vacuum drying method as antioxidant. Issue 1 (April 2020) - Laeliocattleya, R A; Martati, E; Alwi, A N S; Aulia, L P; Yunianta,
Abstract: The demand for antioxidant beverages made from herbs in the community increases due to the increasing number of types diseases caused by free radicals. One type of potential herbs as antioxidant is corn silk, in the form of corn silk herbal drinks tea. The basic ingredients for making herbal tea drinks is the dried corn silk. However, the temperature and drying time was found to affect the characteristics of herbal tea drinks produced. The purpose of this study was to determine the effect of temperature and drying time with vacuum drying method on the content of bioactive compounds and antioxidant activity of corn silk herbal tea. This study used Randomized Block Design with 3 replications and 2 Factor. Factor 1 is drying temperature (40°C, 50°C and 60°C) and Factor 2 is drying time (3 hours, 4 hours and 5 hours). Each sample was then analysed the bioactive compounds (total phenolics, flavonoids) and antioxidant activity. The study found that the higher of drying temperature resulted on higher phenolics, flavonoids and antioxidant activity. Conversely, drying time showed a declining trend. The best treatment was found from the combination of drying temperature at 60°C with 4 hours drying time, giving the total phenolics of 11.68 mg GAE/g, flavonoids of 6.47 mg QE/g and antioxidant activity with IC50 values of 278.1 ppm, respectively.